Phylogeny, diversity, and biogeography of Southeast Asian spiny rats (Maxomys). - Anang Setiawan, Achmadi; J. A., Esselstyn; K.C., Rowe; I., Maryanto; Mohd Tajuddin, Abdullah (Journal of Mammalogy, 2013)
Knowledge of the diversity and relationships of species in many groups of plants and animals in Southeast Asia is severely limited, preventing an integrative understanding of evolutionary and ecological processes in island archipelagos. We generated a 3-locus DNA sequence data set to estimate phylogenetic relationships among species and populations of Maxomys, a genus of rodents endemic to Southeast Asia. Our inclusion of Crunomys as a potential outgroup supported the monophyly of Crunomys, but the genus was deeply nested within Maxomys. Because of the relatively ancient divergences (mean uncorrected p-distances up to 0.15 in cytochrome-b sequences) among species of Maxomys and short branch lengths among basal lineages of the phylogeny, we obtained little support for the oldest relationships in Maxomys + Crunomys. However, our analyses revealed unrecognized diversity in the form of divergent populations both between and within islands and the presence of 2 potentially undescribed species from Sulawesi. The Maxomys and Crunomys of Sulawesi belonged to 4 clades sister to extralimital species, suggesting that repeated overwater dispersal between Sundaland–Philippines and Sulawesi was an important isolating mechanism in the history of this group.